Design, Analysis and Construction of a Steel Truss Cable-Stayed Bridge for High-Speed Railway in China. Issue 4 (1st November 2016) - He, Xuhui; Qin, Hongxi; Liu, Wenshuo; Frank Chen, Y.; Zhai, Jianping; Yu, Lang
Abstract: The Yujiang cable-stayed bridge, a significant project of the Nanning–Guangzhou High-Speed Railway, consists of steel-truss girders and two symmetrical vase-shaped concrete pylons up to 102.5 m high. With a main span of 228 m, the bridge crosses the main shipping channel of the Yujiang River. In this paper, the key design criteria and structural details are reviewed and discussed along with the special design considerations, including pylon local stress distribution, vehicle–bridge interaction, seismic response and wind tunnel experiment. In addition, a new construction method involving synchronous construction technology of tower and girder is introduced.